2023
DOI: 10.1001/jamasurg.2022.6387
|View full text |Cite
|
Sign up to set email alerts
|

Association of Frailty With Health-Related Quality of Life in Liver Transplant Recipients

Abstract: ImportanceFrailty has been recognized as a risk factor for mortality after liver transplant (LT) but little is known of its association with functional status and health-related quality of life (HRQL), termed global functional health, in LT recipients.ObjectiveTo evaluate the association between pre-LT and post-LT frailty with post-LT global functional health.Design, Setting, and ParticipantsThis prospective cohort study was conducted at 8 US LT centers and included adults who underwent LT from October 2016 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…A recent report from the multicenter Functional Assessment in Liver Transplantation (FrAILT) consortium showed that LT recipients with pretransplant frailty were more likely to exhibit physical frailty after LT, had lower odds of employment and had lower self-reported physical functioning. Only 5% of frail pretransplant recipients were robust at 1-year post-transplant, highlighting the need to developed tailored pretransplant interventions 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report from the multicenter Functional Assessment in Liver Transplantation (FrAILT) consortium showed that LT recipients with pretransplant frailty were more likely to exhibit physical frailty after LT, had lower odds of employment and had lower self-reported physical functioning. Only 5% of frail pretransplant recipients were robust at 1-year post-transplant, highlighting the need to developed tailored pretransplant interventions 25 …”
Section: Discussionmentioning
confidence: 99%
“…Only 5% of frail pretransplant recipients were robust at 1-year post-transplant, highlighting the need to developed tailored pretransplant interventions. [25] Behavior change is difficult and notoriously so in the setting of decompensated liver disease, whereby patients suffer from weakness, fatigue, anhedonia, and impaired mobility in addition to symptoms of cramping and volume overload. A growing body of evidence supports the use of small financial incentives to promote physical activity among healthy adults as well as those with chronic conditions such as solid organ transplant recipients and patients with ischemic heart disease.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…Frailty has been shown to have a considerable negative economic impact on the hospital system and on patients' families. 4 If more emphasis were placed on prehabilitation or on early postoperative rehabilitation, as suggested in this study 3 as means to improve compliance, there could be a considerable positive economic impact on hospital systems. This includes postdischarge rehabilitation care, physical therapy, home nursing visits, and skilled nursing facilities, which are underused by many transplant centers.…”
Section: Related Article Page 130mentioning
confidence: 92%
“…The difficulty in liver disease, though, is that sarcopenia and frailty are a result of end-stage liver disease and commonly the only option for survival is liver transplant, especially when a patient is severely decompensated and with inpatient treatment status. The model presented by Lai et al 3 works well for outpatients, but in the current allocation scheme, patients are commonly inpatient when undergoing transplant and this population is not addressed in this series.…”
mentioning
confidence: 99%
See 1 more Smart Citation